EFL Students’ Perceptions of the Cake in Enhancing Speaking Skills: A Student-Centered Approach - Aisyah, Putri Nur; Farida Repelita Waty Br. Kembaren (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study investigated EFL students’ perceptions of using the Cake application as a pedagogical tool to enhance English speaking skills, employing a qualitative, student-centered approach. The data were collected using two modified questionnaires and semi-structured interviews. A purposive sampling method is applied to select the research participants. Thematic content analysis was applied to interpret the data. The research participants consist of 39 EFL students enrolled at one of the State Senior High Schools in Medan who have played Cake more than twice. The findings revealed that most students perceive the Cake app positively, citing improvements in vocabulary acquisition, pronunciation, confidence, and engagement in language learning. Key advantages included interactive features, flexible access, and enjoyable learning experiences. However, limitations such as a lack of grammar instruction in sufficient writing support and internet dependency were also reported. The study suggests that integrating a mobile language learning tool, such as Cake, into a dynamic environment can significantly support the development of speaking proficiency.